Răspuns :
a+b+c=103
a=4b
c=a-b+7 inlocuind a doua relatie in a treia c=4b-b+7=3b+7
inlocuind a doua si a treia relatie in prima relatie obtii: 4b+b+3b+7=103
8b=96
b=12
a=4*12=48
c=48-12+7=43
a=4b
c=a-b+7 inlocuind a doua relatie in a treia c=4b-b+7=3b+7
inlocuind a doua si a treia relatie in prima relatie obtii: 4b+b+3b+7=103
8b=96
b=12
a=4*12=48
c=48-12+7=43
[tex]a+b+c=103 \\ a=4b \\ c=(a-b)+7 \\ c=(4b-b)+7=\ \textgreater \ c=3b+7 \\ 4b+b+3b+7=103 \\ 8b=103-7 \\ b=96:8 \\ b=12 \\ a=4*12=48 \\ c=3*12+7=43[/tex]